Reoperative mitral valve surgery via sternotomy or right thoracotomy: A propensity‐matched analysis. Issue 10 (2nd August 2019) - Patel, Nirav C.; Hemli, Jonathan M.; Seetharam, Karthik; Graver, L. Michael; Brinster, Derek R.; Pirelli, Luigi; Scheinerman, S. Jacob; Hartman, Alan R.
Abstract: Background: There is, as yet, no broad consensus regarding the optimal surgical approach for patients requiring reoperative mitral valve surgery. Consequently, we sought to evaluate the perioperative outcomes for patients undergoing redo mitral surgery via right mini thoracotomy as compared with traditional resternotomy. Methods: A comprehensive retrospective review of our prospectively collected database was undertaken from January 2011 to December 2017. We propensity matched 90 patients who underwent reoperative mitral valve surgery via right mini thoracotomy with a concurrent cohort of patients who had redo median sternotomy. Intraoperative data and short‐term clinical outcomes were analyzed. Results: The 30‐day mortality was 3.3% (six deaths) in the entire cohort, not significantly different between redo sternotomy and mini thoracotomy groups. Patients who had their procedure via right mini thoracotomy had reduced intensive care unit ( P = .029) and overall hospital ( P < .0001) lengths of stay, a diminished requirement for perioperative transfusion ( P = .023), and a trend towards faster postoperative extubation. Right thoracotomy patients experienced shorter cardiopulmonary bypass ( P = .012) and cardiac arrest ( P < .0001) times than did the sternotomy cases. Peripheral cannulation was utilized more frequently in the mini thoracotomy group, as were fibrillatory arrest techniques. Conclusion: Reoperative mitral valve surgery via right mini thoracotomy is safe, and is associated with shorter extracorporeal circulation times, reduced transfusion, and faster postoperative recovery.